2020
DOI: 10.1371/journal.pone.0227810
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Columbian zoonotic enteric parasites: An insight into Puerto Rican indigenous culture diets and life styles

Abstract: The pre-Columbian Huecoid and Saladoid cultures were agricultural ethnic groups that supplemented their diets by fishing, hunting and scavenging. Archaeological deposits associated to these cultures contained a variety of faunal osseous remains that hinted at the cultures' diets. The present study identified zoonotic parasites that may have infected these two cultures as a result of their diets. We used metagenomic sequencing and microscopy data from 540-1,400 year old coprolites as well as the zooarchaeologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Although we cannot confirm whether the humans at Janey B. Goode were impacted by the pathogens and parasites that the dogs carried, it is reasonable to infer that they were, given that parasites have been found to be widespread in many ancient human populations 85 , 86 , and given the archaeological evidence that suggests dogs and humans at Janey B. Goode were in close contact 87 . As other studies have noted, a shared diet and environment between companion animals and humans also increases the likelihood of infection by similar parasites and pathogens 5 , 6 , 37 , 85 , 88 .This suggests that humans living in the American Bottom during the Late Woodland to Mississippian periods were also impacted by conditions associated with urbanization. Dogs were an important part of life in the American Bottom during the Late Woodland period, and their coprolites are informative not only about their own diet and health, but that of their human companions as well.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although we cannot confirm whether the humans at Janey B. Goode were impacted by the pathogens and parasites that the dogs carried, it is reasonable to infer that they were, given that parasites have been found to be widespread in many ancient human populations 85 , 86 , and given the archaeological evidence that suggests dogs and humans at Janey B. Goode were in close contact 87 . As other studies have noted, a shared diet and environment between companion animals and humans also increases the likelihood of infection by similar parasites and pathogens 5 , 6 , 37 , 85 , 88 .This suggests that humans living in the American Bottom during the Late Woodland to Mississippian periods were also impacted by conditions associated with urbanization. Dogs were an important part of life in the American Bottom during the Late Woodland period, and their coprolites are informative not only about their own diet and health, but that of their human companions as well.…”
Section: Discussionmentioning
confidence: 68%
“…Stable isotope analyses can be used to infer the protein sources and types of plants consumed, and provide a complementary, broader view of an organism’s diet. Recent studies of coprolites, bone and dental calculus using a combination of archaeological, isotopic and genetic methods revealed a wealth of information about ancient human populations in Italy 35 , Argentina 36 , Puerto Rico 37 , and eastern North America 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Coprolites from two pre-Columbian cultures, the Huecoid and Saladoid, recovered in Puerto Rico have previously been characterized by our group to determine the gut microbiota [17,18], viral communities [19] and parasite composition [21], to further support archaeological evidence suggesting that two pre-Columbian populations, the Huecoid and Saladoid, were two different cultures. Prior the 1980s, most of the archaeological evidence suggested that the Huecoid and Saladoid were the same culture.…”
Section: Introductionmentioning
confidence: 76%
“…Some techniques have been tested in an attempt to recover parasites and plants from archeological remains. The study of parasites and diet in archeological material has recently produced combined information about the health and survival conditions of the ancient populations (Moore et al, 2020; Sawafuji et al, 2020; Søe et al, 2018; Wiscovitch-Russo et al, 2020). The data achieved until now, however, could not provide direct information of helminth infection associated with burial in sambaquis archeological site.…”
Section: Introductionmentioning
confidence: 99%